Aquaporin 5 Expression in Mouse Mammary Gland Cells Is Not Driven by Promoter Methylation. (12th February 2015) - Arbeithuber, Barbara; Thuenauer, Roland; Gravogl, Yasmin; Balogi, Zsolt; Römer, Winfried; Sonnleitner, Alois; Tiemann-Boege, Irene
Abstract : Several studies have revealed that aquaporins play a role in tumor progression and invasion. In breast carcinomas, high levels of aquaporin 5 (AQP5), a membrane protein involved in water transport, have been linked to increased cell proliferation and migration, thus facilitating tumor progression. Despite the potential role of AQP5 in mammary oncogenesis, the mechanisms controlling mammary AQP5 expression are poorly understood. In other tissues, AQP5 expression has been correlated with its promoter methylation, yet, very little is known about AQP5 promoter methylation in the mammary gland. In this work, we used the mouse mammary gland cell line EpH4, in which we controlled AQP5 expression via the steroid hormone dexamethasone (Dex) to further investigate mechanisms regulating AQP5 expression. In this system, we observed a rapid drop of AQP5 mRNA levels with a delay of several hours in AQP5 protein, suggesting transcriptional control of AQP5 levels. Yet, AQP5 expression was independent of its promoter methylation, or to the presence of negative glucocorticoid receptor elements (nGREs) in its imminent promoter region, but was rather influenced by the cell proliferative state or cell density. We conclude that AQP5 promoter methylation is not a universal mechanism for AQP5 regulation and varies on cell and tissue type.